Optimalization Stock Portfolio Based on Single Index Model over Bullish and Bearish Market: Case Study on LQ45 Manufacturing Company - Yandi Ikadarma; Eka Bertuah (Penerbit Kemala Indonesia, 2019)
This study aimed to determine the optimalization stock portfolio as a basis of investment inside company stocks in LQ45 on Indonesia Stock Exchange. In this research, we use data observation from January 2013 to December 2017 with quantitative method to obtain population over 11 manufacturing companies based single index model. The results showed 5 stocks became to portfolio candidates from the 11 candidate stocks studied which is 5 optimal portfolio shares had a return of 0.019 or equal 1.98% per month. Here, the 5 optimal portfolio have a risk and must be faced by investors shares around 0.007 or equal to 0.07%. The 5 optimal portfolio namely UNVR, ICBP, GGRM, KLBF, and INDF to share over investors. The fund proportion can be invested by 5 shares such as UNVR, ICBP, GGRM, KLBF, and INDF are equal 56.06%, 16.14%, 7.86%, 16.42% and 3.52%, respectively. The Return on bullish conditions shows that the portfolio returns is calculated from selected five stocks to obtain optimal portfolio formation reached 0.021. Furthermore, the return on bearish conditions have risk value more than 0.008. Thus, the optimal portfolio in bullish conditions can reduced investment risk more than 0.011 poins. Thus, the optimal portfolio can be reduced risk value over low level in bearish conditions in LQ45 manufacturing company in near future